Trust in Private Security: Current Research in Finland - Saarikkomäki Elsa; Paasonen Jyri; Haarla Sanna (Springer, 2025)
Finland as a Nordic welfare state traditionally has a strong emphasis on the state and its police and trust in the police is exceptionally high. Recently, global changes in policing landscape and pluralization of policing have occurred as the private sector participates in delivering security in private, public, and quasi-public spaces. However, even globally, we do not have much information on how these changes in the policing landscape affect trust and how citizens perceive private policing. This chapter points out that trust in private policing is important to study. It suggests that in addition to general trust, trust created or challenged in specific encounters between private policing agents and citizens, particularly among vulnerable groups, is important to consider. We start by describing the current context of the plural policing landscape in Finland. Secondly, we present current empirical research considering (a) citizens’ general trust in private policing, (b) experiences of typical objects of policing, young people, and ethnic minorities, and (c) victimization of security guards at their work. Throughout this chapter, we compare the empirical findings of private security in relation to police. Finally, we suggest some ways of how to improve trust. This paper offers new insights for an international audience from different empirical fields of study and contexts, and it maps out future research agendas to further develop trust in policing.
Plural Policing in the Global North: Insights into Concepts, Aspects and Practices